Reappraisal of intracerebral hemorrhages and intracerebral hemorrhage grading scale score in surgically and medically managed cerebellar intracerebral hemorrhage - Won, Sae-Yeon; Walter, Johannes; Hernandez-Duran, Silvia; Alhalabi, Obada; Behmanesh, Bedjan; Bernstock, Joshua D.; Czabanka, Marcus; Dinc, Nazife; Dubinski, Daniel; Flüh, Charlotte; Freiman, Thomas M.; Grosch, Anne S.; et al. (Neurosurgery, 2023)
BACKGROUND: - As compared with supratentorial intracerebral hemorrhages (ICH), bleeds that occur within the cerebellum require special consideration given the nature of the posterior fossa. - OBJECTIVE: - To validate ICH and ICH grading scale (ICH-GS) scores in patients with cerebellar hemorrhage and examine the outcomes of patients managed surgically as compared with those who underwent conservative treatment. - METHODS: - This observational multicenter study included 475 patients with cerebellar hemorrhage from 9 different neurosurgical departments in Germany between 2005 and 2021. The prognostic accuracy of ICH and ICH-GS scores were calculated by the area under the curve of the receiver operating characteristic curves. Analyzed outcomes were the in-hospital mortality, mortality at 6 months, in-hospital outcome, and outcome at 6 months. - RESULTS: - Of 403 patients, 252 patients (62.5%) underwent surgical treatment and 151 patients (37.5%) conservative treatment. Both ICH and ICH-GS scores demonstrated good prognostic accuracy regarding both overall mortality and functional outcomes. In those patients presenting with severe cerebellar hemorrhages, ie, ICH score >3 and ICH-GS score >11, overall mortality was significantly lower in surgically treated patients. Mortality was significantly higher in those patients managed surgically who presented with ICH scores ≤3; in such patients, improved outcomes were noted when the hematoma was treated conservatively. - CONCLUSION: - ICH and ICH scores are useful tools for prediction of survival and outcome in patients with cerebellar ICH. Surgical management may be beneficial for those who present with severe cerebellar ICH as reflected by ICH scores >3, while conservative management seems reasonable in patients with lower ICH scores.
Gesehen am 06.07.2023